Seasonal Migration and Early Childhood Development - Macours, Karen; Vakis, Renos (2012)
This paper provides unique evidence of the positive consequences of seasonal migration for investments in early childhood development. We analyze migration in a poor shock-prone border region in rural Nicaragua where it offers one of the main household income diversification and risk-coping strategies. IV estimates show, somewhat surprisingly, that shock-driven migration by mothers has a positive effect on early cognitive development. We attribute these findings to changes in income and to the intra-household empowerment gains resulting from mother's migration, which offset potential negative early childhood development effects from temporary lack of parenting.